1991
DOI: 10.1088/0268-1242/6/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of polysilicon film growth by thermal decomposition of silane

Abstract: Several mechanisms for deposition of polysilicon layers by thermal decomposition of silane, in which the transfer of silicon to the surface of growth is accomplished by silane. sililene or disilane, are discussed. It is shown that under defined prerequisites, application of the Langmuir-Hinshelwood model for the acting surfaces in the three cases leads to a kinetic relationship for the growth rate as a function of Silane concentration. The temperature dependences of t h e Constants in t h e relationship for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…In addition, measurements of the deposition rate on planar surfaces as a function of growth temperature indicated that the activation energy (E) for film deposition is 1.4 eV. Both n and E are consistent with the calculations and experiments of other authors [28,29].…”
Section: Resultssupporting
confidence: 88%
“…In addition, measurements of the deposition rate on planar surfaces as a function of growth temperature indicated that the activation energy (E) for film deposition is 1.4 eV. Both n and E are consistent with the calculations and experiments of other authors [28,29].…”
Section: Resultssupporting
confidence: 88%
“…However, the parameters quoted in Ho et al (1994) and Houf et al (1993) are incompatible with the type space of the present work, and the gas-surface mechanism proposed in those works shows considerable divergence from experimental results at temperatures above 800 1C. A similar observation is made for the surface growth parameters of Peev et al (1991), which diverge above 960 1C.…”
Section: Model Bcontrasting
confidence: 54%
“…These considerations strongly support the qualitative statements in section 4.2. Using the calculated silicon deposition rates in combination with CVD data from the literature, 49 it is possible to estimate mean silane concentrations close to the wall for different experiments. Although the kinetic data have to be extrapolated in terms of temperature, this will not lead to an essential error because the temperature is the same for every considered case except one.…”
Section: Resultsmentioning
confidence: 99%